Japan and the IISS Connecting Western and Japanese Strategic Thought from the Cold War to the War on Ukraine - Ward, Robert (Robert Alan); Koshino, Yuka; Lebreton, Matthieu (Adelphi series, 2023)
Strategic links between Japan and Europe during the Cold War were limited. During this period the IISS helped bridge the gap between the two, exposing its membership base to the international affairs of Asia and Japan and providing Japanese scholars, strategists and diplomats with a platform from which to amplify their voices in the West. Analyses by these experts often appeared in IISS publications, but the Institute also gained key insights through its well-established conferences and lecture series. These initiatives illuminated Japanese strategic thinking and perspectives on contemporary critical issues in Japan's and Asia's foreign, security and defence policy. This Adelphi book, through its collection of earlier analysis, helps the reader to understand the evolution of Japanese strategic thought from the 1960s until today, and shines a light on the continuities and changes in this thinking. New, original analysis of the material seeks to identify areas where such thinking was prescient and remains relevant to the contemporary strategic environment, and other areas where predictions failed or assumptions were proved wrong. These new essays were also informed by interviews of Japanese senior scholars and diplomats who spent time with the IISS. This book seeks to frame, educate and guide strategic thinking on the most pressing issues of today, both in and outside Japan and Asia, and will be of great interest to analysts, practitioners and students of international affairs.